Kepemimpinan Transformasional Kepala Sekolah untuk Membangun Budaya Literasi Membaca di Lingkungan Sekolah Negeri - Marliansyah, Anan; Suwadi, Suwadi (Program Studi Manajemen Pendidikan Islam UIN Sunan Ampel Surabaya, 2024)
The principal is a leader figure in the school environment. The principal’s transformational leadership has an influence on the reading literacy culture in the school environment. Researchers in this study collected data from library data and from journals and books which are better known as library studies.researchers analyze research content related to the theme being researched to draw conclusions. The research result show that the principal’s transformational leadership builds a good and efficient literacy culture. The principal’s transformational leadership is able to change the school’s potential to have a high literacy culture. The ability possessed by the principal’s transformational leadership is in the form of innovation ability, innovation is useful for encouraging the emergence of new breakthroughs in education. The motivation, motivation is useful for encouraging student’s enthusiasm in the educational process and fostering the work ethic of their educators. And inspiration, inspiration is useful for fostering high passion for all school staff. The school principal’s transformational leadership abilities are able to have an effect on students and girls in the school to enjoy reading and in general can foster a culture of literacy for all members of the school.